Evaluating the implementation and effectiveness of a multi-component intervention to reduce post-surgical opioid prescribing: study protocol of a mixed-methods design - Karl Y Bilimoria; Jonah J Stulberg; Willemijn L A Schäfer; Meagan L Shallcross; Bruce L Lambert; Reiping Huang; Jane L Holl; Julie K Johnson (BMJ Open, 2019)
IntroductionOpioids prescribed after surgery accounted for 5% of the 191 million opioid prescriptions filled in 2017. Approximately 80% of the opioid pills prescribed by surgical care providers remain unused, leaving a substantial number of opioids available for non-medical use. We developed a multi-component intervention to address surgical providers’ role in the overprescribing of opioids. Our study will determine effective strategies for reducing post-surgical prescribing while ensuring adequate post-surgery patient-reported pain-related outcomes, and will assess implementation of the strategies.Methods and analysisThe Minimising Opioid Prescribing in Surgery study will implement a multi-component intervention, in an Illinois network of six hospitals (one academical, two large community and three small community hospitals), to decrease opioid analgesics prescribed after surgery. The multi-component intervention involves four domains: (1) patient expectation setting, (2) baseline assessment of opioid use, (3) perioperative pain control optimisation and (4) post-surgical opioid minimisation. Four surgical specialities (general, orthopaedics, urology and gynaecology) at the six hospitals will implement the intervention. A mixed-methods approach will be used to assess the implementation and effectiveness of the intervention. Data from the network’s enterprise data warehouse will be used to evaluate the intervention’s effect on post-surgical prescriptions and a survey will collect pain-related patient-reported outcomes. Intervention effectiveness will be determined using a triangulation design, mixed-methods approach with staggered speciality-specific implementation for contemporaneous control of opioid prescribing changes over time. The Consolidated Framework for Implementation Research will be used to evaluate the site-specific contextual factors and adaptations to achieve implementation at each site.Ethics and disseminationThe study aims to identify the most effective hospital-type and speciality-specific intervention bundles for rapid dissemination into our 56-hospital learning collaborative and in hospitals throughout the USA. All study activities have been approved by the Northwestern University Institutional Review Board (ID STU00205053).